2014
DOI: 10.1016/j.egypro.2014.11.489
|View full text |Cite
|
Sign up to set email alerts
|

Rapid solubility and mineral storage of CO2 in basalt

Abstract: The long-term security of geologic carbon storage is critical to its success and public acceptance. Much of the security risk associated with geological carbon storage stems from its buoyancy. Gaseous and supercritical CO 2 are less dense than formation waters, providing a driving force for it to escape back to the surface. This buoyancy can be eliminated by the dissolution of CO 2 into water prior to, or during its injection into the subsurface. The dissolution makes it possible to inject into fractured rocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 43 publications
0
52
0
Order By: Relevance
“…Instead we only observed growth of the calcium carbonate polymorphs, calcite, and aragonite. The growth of the Ca‐carbonates is not surprising and has been shown to occur during CO 2 ‐basalt interactions over a range of temperatures . Rogers et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead we only observed growth of the calcium carbonate polymorphs, calcite, and aragonite. The growth of the Ca‐carbonates is not surprising and has been shown to occur during CO 2 ‐basalt interactions over a range of temperatures . Rogers et al .…”
Section: Discussionmentioning
confidence: 99%
“…The growth of the Ca-carbonates is not surprising and has been shown to occur during CO 2 -basalt interactions over a range of temperatures. 43,44 Rogers et al 27 found that calcite is the only carbonate that is commonly found associated with basalt weathering and low temperature alteration in Iceland. This natural weathering however occurs at low temperatures and also at lower CO 2 pressures, preventing the formation of Mg-carbonates such as dolomite and magnesite (high activation energies prevent low-temperature formation).…”
Section: Discussionmentioning
confidence: 99%
“…Basaltic rocks form approximately 8% of the continents and much of the ocean floor. Therefore, there is an enormous potential CO2 storage capacity in basaltic rocks [109]. The key positive aspects of their potential for CO2 storage are their high reactivity and abundance of divalent metal ions in such rock which can potentially fix CO2 for geological timescales [110].…”
Section: Basalt Formationsmentioning
confidence: 99%
“…This NET may not become legal to implement. (7) Subsurface mineralization, forming carbonate minerals by direct injection of dissolved CO 2 to contact reactive minerals in the subsurface, has been successfully trialled at a very small pilot [59]. Scale up during a 10 year period, using conventional technology could increase this to significant impact, although long-term evolution of porosity and permeability, thus sustainability of this storage method, has yet to be proven.…”
Section: Summary and Proposals For Actionmentioning
confidence: 99%